Pendidikan Rohani Anak Di Gereja Bethel Tabernakel Ngaliyan Semarang - Eni Rombe; Didasgil SI Taneo; Disetra Fiser Manik (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
Spiritual education for children at the Beth-El Tabernacle Church in Ngaliyan, Semarang aims to shape Christ-like character in them, encouraging children to know and accept Jesus Christ as their Lord and Savior. Children are taught to understand and practice God's Word in their daily lives, grow in faith, and participate in church services. To support this goal, the PkM team conducted community service activities during the odd semester of 2023/2024 at GBT Ngaliyan, Semarang. This activity, titled